Waterproof Minimalist Coffee Table - Chan, Yi Qing; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2023)
Floods are becoming more severe in Malaysia, and the number of floods is increasing year after year. The flood events will cause harm to the human as well as the furnishings. Direct contact with water may change the structure and exterior appearance of a product, especially if it is constructed of a non-water-resistant material like MDF or plywood. Therefore, the goal of this study is to determine design criteria, design and fabricate a minimalist coffee table that is waterproof. The questionnaire was completed by Selangor citizens aged 21 and above in order to determine the coffee table’s design criteria. Following that, the coffee table design process began with visual research, progressed through thumbnail and ideation sketches, idea development, final design selection, mock-up development, and concluded with prototype fabrication. The coffee table prototype in the present study was built of rubber wood and stainless steel. Sealer and lacquer are the finishes used on coffee tables parts made of rubber wood. Three criteria influence the design of the coffee table, which is a rectangle coffee table, a natural color coffee table, and a combination of wood and metal criteria. As a solution to the aforementioned challenge, this study successfully designed a minimalist coffee table with waterproof ability that fulfills market demand.